CREATING IMAGES OF REALITY IN STATUTORY INSTRUMENTS - LIZISOWA, Maria Teresa (Comparative Legilinguistics, 2014)
The article presents the subjectivity of semantic signs of the legislative language as images of reality in a statutory instrument. The author presents a semantic and pragmatic analysis of the meaning and communicative function of language signs taking into account the techniques of expressing meanings in legal provisions. The analysis of grammatical structures and style of statutory instruments reveals the artificiality of references of terms, attributes and syntactical structures expressing cause and effect relations in expressions typical of the legislative language and conveying connoted messaged in a non-verbatim way.